Social-philosophical and educational aspects of globalization - KRYMETS, L.V. (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article provides total globalization, the problem of managing world processes, including world culture and world public opinion, becomes one of the central objectives of humankind in the development of modern education